A new understanding of formal land use plans in Germany. (1st January 2011) - Allin, Simone
Traditionally, German local land use plans focus on issues such as zoning, transportation, social and green infrastructure planning. Nowadays, they are criticised to be too inflexible and – especially in respect of content – too limited to cope with the pace and complexity of various interacting subprocesses and actors of urban development. Accordingly, collaborative and strategic tasks of planning at the local scale require a more comprehensive and integrative understanding of the contents of land use plans and their subsequent levels of intervention. Referring to the overall goal of sustainable urban development, the complexity of addressing the needs of various individual groups of actors can be taken as an example for the challenges currently faced by traditional land use plans. This paper focuses on the question of how the different levels of intervention of formal land use plans can be described in a broader sense. This approach, particularly, includes the analysis of the role of these plans within the governance of organisations, institutions and human behaviours. Furthermore, these issues are highly relevant in the specific context of urban decline and city shrinkage in Eastern Germany. This paper suggests amendments to the model of the German local land use plan and outlines future directions of research.